Neutrophil-to-lymphocyte ratio as a prognostic indicator in COVID-19: Evidence from a northern tanzanian cohort - Norman Jonas Kyala; Innocent Mboya; Elichilia Shao; Francis Sakita; Kajiru Gadiel Kilonzo; Laura Shirima; Abid Sadiq; Elifuraha Mkwizu; Nyasatu Chamba; Annette Marandu; Sophia Muhali; Faryal Raza; et al. (PLoS ONE, 2025)
Background COVID-19 caused a profound global impact, resulting in significant cases and deaths. The progression of COVID-19 clinical manifestations is influenced by a dysregulated inflammatory response. Early identification of the subclinical progression is crucial for timely intervention and improved patient outcomes. While there are various biomarkers to predict disease severity and outcomes, their accessibility and affordability pose challenges in resource-limited settings. We explored the potentiality of the neutrophil-to-lymphocyte ratio (NLR) as a cost-effective inflammatory marker to predict disease severity, clinical deterioration, and mortality in affected patients. Methodology A hospital-based retrospective cohort study was conducted at KCMC Hospital among COVID-19 patients followed from admission to discharge between 1 st March 2020 and 31 st March 2022. NLR was calculated as the absolute neutrophil count in μL divided by the absolute lymphocyte count in μL. The NLR cut-off value was determined using Receiver Operating Characteristic (ROC) analysis and assessed its predictive ability at admission for in-hospital mortality. The Chi-square test compared the proportion of NLR by patient characteristics. The association of NLR with disease severity and mortality was analyzed using the modified Poisson and Cox regression models, respectively. Results The study included 504 patients, with a median age of 64 years, 57.1% were males, and 68.3% had severe COVID-19. The in-hospital COVID-19 mortality rate was 37.7%. An NLR cutoff value of 6.1 or higher had a sensitivity of 92.1% (95% CI 89.2%–94.0%) and a specificity of 92.0% (95% CI 89.7%–94.4%). Additionally, 39.5% of patients with an NLR value of 6.1 or higher had increased risk of severe disease, subsequent clinical deterioration, and mortality. Conclusion and recommendation An NLR value of 6.1 or higher at the time of hospital admission associated with severe disease, clinical deterioration, and mortality in patients with COVID-19. Integration of NLR as a prognostic parameter in COVID-19 prognosis scales could improve risk assessment and guide appropriate management strategies for COVID-19 patients, as well as for potential future viral-related pneumonias. Further prospective studies are necessary to validate these findings and evaluate the clinical utility of NLR in larger cohorts of patients.